2004
DOI: 10.1097/00054725-200411000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Autoantibodies in Inflammatory Bowel Disease

Abstract: The prevalence of PAB found in CD patients in this study was similar to that cited in previous reports. In contrast to these reports, we also found an increased prevalence of PABs in patients with UC and in unaffected first-degree relatives of IBD patients. We observed two main staining patterns, both of which were present in IBD and were associated with specific phenotypes of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
1
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 29 publications
5
40
1
1
Order By: Relevance
“…The specificity for CD in the present study compared to both control groups was as high as 92%-95% with a strong positive likelihood ratio of 5.14 -8.77 against controls. However, a more recent study from Belgium found a much higher prevalence (22.2%) of PAB in UC, 35 in agreement with findings from the present study (22.7%). Consequently, the specificity for CD in the present study compared to UC decreased to 76%-77%.…”
Section: Discussionsupporting
confidence: 93%
“…The specificity for CD in the present study compared to both control groups was as high as 92%-95% with a strong positive likelihood ratio of 5.14 -8.77 against controls. However, a more recent study from Belgium found a much higher prevalence (22.2%) of PAB in UC, 35 in agreement with findings from the present study (22.7%). Consequently, the specificity for CD in the present study compared to UC decreased to 76%-77%.…”
Section: Discussionsupporting
confidence: 93%
“…Serum reactivity against mycobacterial antigens has also been correlated with human autoimmune diseases including Crohn's disease (13). Moreover, pancreatic antibodies are associated with Crohn's disease (9).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it is interesting to note, that almost all type 2 PAB positive sera also show a weak type 1 PAB staining by IIF at least on human pancreas [43]. Furthermore, type 2 PAB does not seem to differentiate CrD patients from UC patients whereas type 1 PAB appears to be able do so [32]. In fact, anti-GP2 reactivity is not universally found in all PAB-positive patients.…”
Section: Identification Of Crd-specific Pancreatic Autoantigensmentioning
confidence: 93%
“…A multicenter study involving 109 CrD patients from five university hospitals in France and one in Luxemburg, failed to identify an association between PABs and clinical features of the disease except of a relationship between the presence of the autoantibodies and an early disease onset [30]. An earlier study from Leuven including 169 CrD patients established a significant negative association of stricturing disease behavior and PAB seropositivity [32].…”
Section: Autoimmunity In Crohn's Diseasementioning
confidence: 95%